MitraClip and left ventricular reverse remodelling: a strain imaging study. (20th May 2020) - Papadopoulos, Konstantinos; Ikonomidis, Ignatios; Chrissoheris, Michael; Chalapas, Antonios; Kourkoveli, Panagiota; Parissis, John; Spargias, Konstantinos
Abstract: Aims: The purpose of this study is to identify echocardiography predictors of clinical response and reverse left ventricular (LV) remodelling in patients with functional mitral regurgitation (FMR) treated with MitraClip. Method and results: We retrospectively analysed 86 high surgical risk patients with severe FMR; of those, 58 were implanted a MitraClip, and 28 received medical treatment and served as controls. At baseline and at 1‐year follow‐up, we performed clinical and echocardiography evaluation to assess global longitudinal strain (GLS) and myocardial work [global work index (GWI), global constructive work (GCW), global wasted work (GWW), global work efficiency (GWE)]. Mitral regurgitation was significantly reduced after MitraClip implantation (3.7 ± 0.4 vs. 1.7 ± 0.8, P < 0.001), and the procedure was associated with improvement in brain natriuretic peptide levels (980 ± 1027 vs. 420 ± 338 pg/mL, P < 0.001), New York Heart Association class status (3.2 ± 0.55 vs. 2.0 ± 0.6, P < 0.001), 6‐min walking test (233 ± 154 vs. 286 ± 114 m, P = 0.01) at follow‐up and reduction of left ventricle end‐systolic (LVESV) and left ventricle end‐diastolic volumes (LVEDV) (152 ± 68 vs. 136 ± 43 mL, P = 0.004 & 219 ± 74 vs. 193 ± 66 mL, P = 0.001, respectively). MitraClip procedure was associated with improvement of LV performance and significant increase of GWI (607 ± 282 vs. 650 ± 260 mmHg%, P = 0.045) and GCW (854 ± 288 vs. 949 ± 325 mmHg%, P < 0.001). Baseline ejection fraction (EF), GLS, GWI, GCW, and effective regurgitant orifice area were the variables that were associated with reduction of LVEDV 1 year after intervention ( P < 0.05 for all) and baseline GCW of the LV was the only variable associated with reduction of LVESV ( P = 0.002). Receiver operating characteristic curve analysis identified that a GLS cut‐off value of −8.65% (AUC 0.815, P = 0.007) was associated with a 20% reduction of the LVEDV with a sensitivity and specificity of 72% and 70%, respectively, and that a GCW cut‐off value of 846 mmHg% (AUC 0.759, P = 0.007) was associated with a 10% reduction of LVESV with sensitivity and specificity 79% and 74%, respectively. Conclusions: Mitral valve repair with MitraClip has positive clinical and echocardiographic impact in patients with FMR 1 year after implantation. Preserved GLS and GCW values appear to be associated with LV reverse remodelling post intervention.